POTENSI DAN TANTANGAN NELAYAN KECAMATAN LEKOK KABUPATEN PASURUAN - Basit, Abdul; Zulaecho, Dwi Putri; Nur Azizah, Mundiah (Journal of Economics and Regional Science, 2026)
Lekok Subdistrict, located in the coastal area of Pasuruan Regency, is one of the regions with significant marine fisheries potential. Fishing activities in this area serve as a primary source of livelihood for the local community. This study aims to identify the potential of fishery resources and examine the challenges faced by fishermen in conducting their activities. A qualitative approach was used, employing observation, in-depth interviews, and literature review techniques. The results indicate that the fisheries potential in Lekok is abundant, encompassing various types of catch and a strategic location near the Java Sea. However, fishermen face numerous challenges, such as limited access to modern fishing equipment, extreme weather conditions, fluctuating fish prices, and restricted access to markets and business capital. Additionally, coastal environmental degradation and conflicts among marine resource users pose significant obstacles. Therefore, collaborative efforts between the government, non-governmental organizations, and fishing communities are needed to enhance fishermen’s capacity and manage coastal resources sustainably